Analisis Perencanaan Pengelolaan Keuangan Desa (Studi Kasus pada Desa Glagahwero Kecamatan Panti Kabupaten Jember) - Syafa Abhinaya Putri; Intan Rizki Ainun Nisa; Felanti Wulandari; Naviza Virda Uci; Meylin Indah Nawang Wulan; Fabella Jihan Salma; Silvina Yusapti Sehatatina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the financial planning and management in Glagahwero Village, Panti Subdistrict, Jember Regency. Based on the Village Law and related regulations such as Ministry of Home Affairs Regulation (Permendagri) No. 20 of 2018 and No. 114 of 2014, this research highlights the steps involved in the planning, execution, and reporting of village finances. A qualitative approach was used with a case study involving interviews with village officials and analysis of relevant documents. The results show that the village's financial planning aligns with current regulations, though challenges remain in its implementation, such as limited understanding of new regulations among village officials and social issues related to the use of private land. This study emphasizes the importance of improving regulatory understanding and increasing community participation in the village financial planning process to achieve optimal transparency and accountability.